Ictal-Interictal Continuum: When to Worry About the Continuous Electroencephalography Pattern - Cormier, Justine; Maciel, Carolina B.; Gilmore, Emily J. (Seminars in Respiratory and Critical Care Medicine, 2017)
Continuous electroencephalography (cEEG) monitoring is an invaluable tool in the evaluation of encephalopathy and coma in critically ill patients. Marked increases in cEEG monitoring, coinciding with several societal guideline statements in the last decade, have allowed earlier detection and treatment of clearly harmful patterns, including nonconvulsive seizures (NCSz) and nonconvulsive status epilepticus (NCSE). However, it has also unmasked a range of EEG patterns of less clear clinical significance, with some more “malignant” than others given their potential association with increased neuronal stress and secondary brain injury. These patterns lay on a spectrum often referred to as the ictal-interictal continuum (IIC). To date, no definitive guidelines exist for the management of these potentially harmful EEG patterns, thus presenting a clinical dilemma for critical care physicians. Here, we review the various IIC patterns, their associated features, seizure risk, and outcomes and also propose a clinical approach to management based on the available data and expert opinion.
Keywords: ictal-interictal continuum; periodic discharges; rhythmic delta activity; nonconvulsive status epilepticus; continuous electroencephalography